2016
DOI: 10.1089/aid.2015.0182
|View full text |Cite
|
Sign up to set email alerts
|

Dose Frequency Ranging Pharmacokinetic Study of Tenofovir-Emtricitabine After Directly Observed Dosing in Healthy Volunteers to Establish Adherence Benchmarks (HPTN 066)

Abstract: Oral preexposure prophylaxis (PrEP) trials report disparate efficacy attributed to variable adherence. HPTN 066 was conducted to establish objective, quantitative benchmarks for discrete, regular levels of adherence using directly observed dosing of tenofovir (TFV) disoproxil fumarate (TDF)/emtricitabine (FTC). Healthy, HIV-uninfected men and women were randomized to one of four oral regimens of fixed-dose TDF 300 mg/FTC 200 mg tablet for 5 weeks with all doses observed: one tablet weekly (one/week), one table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
195
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 156 publications
(206 citation statements)
references
References 35 publications
11
195
0
Order By: Relevance
“…dosing regimen and a 4-dose/week regimen (13). That benchmark study found that the 90% sensitivity thresholds for TFV and FTC were 35.5 ng/ml and 49.1 ng/ml, respectively, for the daily dosing regimen and 4.2 and 4.6 ng/ml, respectively, for the 4-dose/week regimen (13).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…dosing regimen and a 4-dose/week regimen (13). That benchmark study found that the 90% sensitivity thresholds for TFV and FTC were 35.5 ng/ml and 49.1 ng/ml, respectively, for the daily dosing regimen and 4.2 and 4.6 ng/ml, respectively, for the 4-dose/week regimen (13).…”
Section: Resultsmentioning
confidence: 97%
“…That benchmark study found that the 90% sensitivity thresholds for TFV and FTC were 35.5 ng/ml and 49.1 ng/ml, respectively, for the daily dosing regimen and 4.2 and 4.6 ng/ml, respectively, for the 4-dose/week regimen (13). Results from the quantitative TFV-FTC assay were available for 163 of 165 HIV-uninfected men who accepted PrEP (end-of-study visits only; two participants did not have samples available for testing).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations